WORST_CASE(Omega(0),?) Initial ITS Start location: l3 0: l0 -> l1 : x^0'=x^post0, y^0'=y^post0, (1-x^0 <= 0 /\ -1-y^0+y^post0 == 0 /\ -x^0+x^post0+y^0 == 0), cost: 1 1: l1 -> l0 : x^0'=x^post1, y^0'=y^post1, (-y^post1+y^0 == 0 /\ x^0-x^post1 == 0), cost: 1 2: l2 -> l0 : x^0'=x^post2, y^0'=y^post2, (-y^post2+y^0 == 0 /\ x^0-x^post2 == 0), cost: 1 3: l3 -> l2 : x^0'=x^post3, y^0'=y^post3, (x^0-x^post3 == 0 /\ y^0-y^post3 == 0), cost: 1 Applied preprocessing Original rule: l0 -> l1 : x^0'=x^post0, y^0'=y^post0, (1-x^0 <= 0 /\ -1-y^0+y^post0 == 0 /\ -x^0+x^post0+y^0 == 0), cost: 1 New rule: l0 -> l1 : x^0'=x^0-y^0, y^0'=1+y^0, -1+x^0 >= 0, cost: 1 Applied preprocessing Original rule: l1 -> l0 : x^0'=x^post1, y^0'=y^post1, (-y^post1+y^0 == 0 /\ x^0-x^post1 == 0), cost: 1 New rule: l1 -> l0 : TRUE, cost: 1 Applied preprocessing Original rule: l2 -> l0 : x^0'=x^post2, y^0'=y^post2, (-y^post2+y^0 == 0 /\ x^0-x^post2 == 0), cost: 1 New rule: l2 -> l0 : TRUE, cost: 1 Applied preprocessing Original rule: l3 -> l2 : x^0'=x^post3, y^0'=y^post3, (x^0-x^post3 == 0 /\ y^0-y^post3 == 0), cost: 1 New rule: l3 -> l2 : TRUE, cost: 1 Simplified rules Start location: l3 4: l0 -> l1 : x^0'=x^0-y^0, y^0'=1+y^0, -1+x^0 >= 0, cost: 1 5: l1 -> l0 : TRUE, cost: 1 6: l2 -> l0 : TRUE, cost: 1 7: l3 -> l2 : TRUE, cost: 1 Eliminating location l2 by chaining: Applied chaining First rule: l3 -> l2 : TRUE, cost: 1 Second rule: l2 -> l0 : TRUE, cost: 1 New rule: l3 -> l0 : TRUE, cost: 2 Applied deletion Removed the following rules: 6 7 Eliminating location l1 by chaining: Applied chaining First rule: l0 -> l1 : x^0'=x^0-y^0, y^0'=1+y^0, -1+x^0 >= 0, cost: 1 Second rule: l1 -> l0 : TRUE, cost: 1 New rule: l0 -> l0 : x^0'=x^0-y^0, y^0'=1+y^0, -1+x^0 >= 0, cost: 2 Applied deletion Removed the following rules: 4 5 Eliminated locations on linear paths Start location: l3 9: l0 -> l0 : x^0'=x^0-y^0, y^0'=1+y^0, -1+x^0 >= 0, cost: 2 8: l3 -> l0 : TRUE, cost: 2 Applied acceleration Original rule: l0 -> l0 : x^0'=x^0-y^0, y^0'=1+y^0, -1+x^0 >= 0, cost: 2 New rule: l0 -> l0 : x^0'=x^0-1/2*n0^2-y^0*n0+1/2*n0, y^0'=y^0+n0, (-1+x^0 >= 0 /\ -3/2+x^0-(-1+n0)*y^0-1/2*(-1+n0)^2+1/2*n0 >= 0 /\ n0 >= 0), cost: 2*n0 Applied deletion Removed the following rules: 9 Accelerated simple loops Start location: l3 10: l0 -> l0 : x^0'=x^0-1/2*n0^2-y^0*n0+1/2*n0, y^0'=y^0+n0, (-1+x^0 >= 0 /\ -3/2+x^0-(-1+n0)*y^0-1/2*(-1+n0)^2+1/2*n0 >= 0 /\ n0 >= 0), cost: 2*n0 8: l3 -> l0 : TRUE, cost: 2 Applied chaining First rule: l3 -> l0 : TRUE, cost: 2 Second rule: l0 -> l0 : x^0'=x^0-1/2*n0^2-y^0*n0+1/2*n0, y^0'=y^0+n0, (-1+x^0 >= 0 /\ -3/2+x^0-(-1+n0)*y^0-1/2*(-1+n0)^2+1/2*n0 >= 0 /\ n0 >= 0), cost: 2*n0 New rule: l3 -> l0 : x^0'=x^0-1/2*n0^2-y^0*n0+1/2*n0, y^0'=y^0+n0, (-1+x^0 >= 0 /\ -3/2+x^0-(-1+n0)*y^0-1/2*(-1+n0)^2+1/2*n0 >= 0 /\ n0 >= 0), cost: 2+2*n0 Applied deletion Removed the following rules: 10 Chained accelerated rules with incoming rules Start location: l3 8: l3 -> l0 : TRUE, cost: 2 11: l3 -> l0 : x^0'=x^0-1/2*n0^2-y^0*n0+1/2*n0, y^0'=y^0+n0, (-1+x^0 >= 0 /\ -3/2+x^0-(-1+n0)*y^0-1/2*(-1+n0)^2+1/2*n0 >= 0 /\ n0 >= 0), cost: 2+2*n0 Removed unreachable locations and irrelevant leafs Start location: l3 Computing asymptotic complexity Proved the following lower bound Complexity: Unknown Cpx degree: ? Solved cost: 0 Rule cost: 0